Hysteretic performance of column-footing joints with steel composite hollow RC columns under cyclic load. (May 2020) - Won, Deokhee; Lee, Jeonghwa; Seo, Jihye; Kang, Young-Jong; Kim, Seungjun
Abstract: For structures such as buildings and bridges to have good performance, it is necessary for them to have suitable column-footing joints. A steel composite hollow RC column, which is a composite element, has an inner tube in the hollow section, and so it needs new types of connecting methods for the column-footing joint part. In this paper, three cases of new types of connecting methods have been proposed. They were evaluated through experimental and FE analysis studies. In addition, after a good connecting method for such column-footing joints was selected, it was then applied to large-scale test specimens, and its performance was verified and further evaluated. Highlights: The purpose of this study is that suggestion of a column-footing connecting method for the steel composite hollow RC column. The connecting method for column-footing joint of three cases were proposed. These were evaluated through experimental and FE analysis studies. To verify the performance of connecting methods, height of 2000 mm and height of 4455 mm specimens were produced. They were evaluated under cyclic loads through an experimental study. The welded coupler connection was evaluated as the best method for the maximum load and the ultimate displacement. Thus, it can be considered to be the safest connecting method for steel-composite hollow RC column–footing connection.